THE EXISTENCE OF SOLUTION OF GENERALIZED EIGENPROBLEM IN INTERVAL MAX-PLUS ALGEBRA - Siswanto, Siswanto (PATTIMURA UNIVERSITY, 2023)
An eigenproblem of a matrix is where and . Vector and are eigenvector and eigenvalue, respectively. General form of eigenvalue problem is with , . Interval maks-plus algebra is and equipped with a maximum ( and plus operations. The set of matrices which its component elements of is called matrices over interval max-plus algebra and denoted by . Let , eigenproblem in interval max-plus algebra is with and . Vector and are eigenvector and eigenvalue, respectively. In this research, we will discuss the generalization of the eigenproblem in interval max-plus algebra. Especially about the existence of solution of generalized eigenproblem in interval max-plus algebra. Keywords: interval max-plus algebra, generalized eigenproblem, the existence of the solution.